Clinical Potential of Regulatory T Cell Therapy in Liver Diseases: An Overview and Current Perspectives - Jeffery, Hannah C.; Braitch, Manjit Kaur; Brown, Solomon; Oo, Ye Htun (Frontiers in Immunology, 2016)
The increasing demand for liver transplantation and the decline in donor organs has highlighted the need for alternative novel therapies to prevent chronic active hepatitis, which eventually leads to liver cirrhosis and liver cancer. Liver histology of chronic hepatitis is composed of both effector and regulatory lymphocytes. The human liver contains different subsets of effector lymphocytes, that are kept in check by a subpopulation of T cells known as Regulatory T cells (Treg). The balance of effector and regulatory lymphocytes generally determines the outcome of hepatic inflammation: resolution, fulminant hepatitis or chronic active hepatitis. Thus, maintaining and adjusting this balance is crucial in immunological manipulation of liver diseases. One of the options to restore this balance is to enrich Treg in the liver disease patients. Advances in the knowledge of Treg biology and development of clinical grade isolation reagents, cell sorting equipment and Good Manufacturing Practice (GMP) facilities have paved the way to apply Treg cells as a potential therapy to restore peripheral self-tolerance in autoimmune liver diseases, chronic rejection and post-transplantation. Past and on-going studies have applied Treg in type-1 diabetes mellitus, systemic lupus erythematosus, graft versus host diseases (GVHD) and solid organ transplantations. There have not been any new therapies for the autoimmune liver diseases for more than three decades; thus the clinical potential for the application of autologous Treg cell therapy to treat autoimmune liver disease is an attractive and novel option. However, it is fundamental to understand the deep immunology, genetic profiles, biology, homing behavior and microenvironment of Treg before applying the cells to the patients.